Land Suitability of Pinus merkusii Jungh et de Vriese on Ex-Standing Area of Tectona grandis Linn. F. - Omo Rusdiana; Rizky Fitri Amalia (Jurnal Silvikultur Tropika, 2012)
West Banyumas Forest Management Unit (WBFMU) is one of the forest management units in working area of Perum Perhutani Unit I Central Java, which has a Corporate Class (CC) of pine trees. Recently, the WBFMU intended to expand the acreage of pine stand in order to increase pine resin production. To achieve this purpose, WBFMU used the former logged over area of teak to be planted by pine. But,  problem arise because the planted pine seedlings showed unappropiate growth. So that, this research was aimed to determine the suitability of pine and limiting factors affecting pine growth in teak stands area at WBFMU. The results show that the suitability of land in the area of the former teak stands in plot 22 B is suitable (S) and plot 25 C is not suitable (N) for the development of P. merkusii according to bonita (site index).